Cultural Context and Children’s Perceptions of Conflict and Peace - Coughlin, Chris; Mayers, Gloysis; Dizard, Jesse; Bordin, Judy (Nurture, 2011)
This is a cross cultural comparison of children’s perceptions of conflict and peace. Thirty children, age 6-10 living in the United States and 33 children, of the same age living in the United Arab Emirates were interviewed and asked to respond to 18 questions concerning war, enemy, and peace. Analysis of responses included assessment of sex, culture, and age similarities and differences. Findings indicate that culture plays a prominent role in the way children experience their world and world events. The findings of this study support taking a cultural context focus towards understanding children’s perceptions and using such insight in helping children learn cooperation and acceptance of others knowing that children see the world from the context in which they live.